Electroacupuncture increases immunoexpression of CB1 and CB2 receptors in experimental model of inflammatory bone loss - Alves, Luiza Clertiani Vieira; Lisboa, Mario Roberto Pontes; da Silveira, Helson Freitas; de Sousa, Luane Macêdo; Gusmão, Jonas Nogueira Ferreira Maciel; Dias, Diego Bernarde Souza; Ervolino, Edilson [UNESP]; Furlaneto, Flávia Aparecida Chaves; Vale, Mariana Lima; Gondim, Delane Viana (Elsevier, 2019)
This study evaluated the participation of CB1 and CB2 receptors in the antiresorptive effect of electroacupuncture (EA) on an experimental model of inflammatory bone loss in rats. 30 rats were divided into five groups: C (control); EP (experimental periodontitis); EA (C+ EA); EP-EA (EP+ EA in the acupoints LI4, LG11, ST36, ST44); EP - EA-sham (EP+ EA in sham acupoints). For the EP groups, a ligature was placed around the right mandibular first molars at day 1. Sessions of EA or EA-sham were assigned every other day. Animals were euthanized at day 11. Histometric analysis was performed to evaluate the percentage of bone area in the furcation area. Immunolabeling patterns in the periodontal tissues and immunofluorescent staining in the trigeminal ganglia and in the trigeminal spinal tract for CB1 and CB2 receptors were performed. It was observed increased bone loss in the furcation in the EP and EP-EA-sham groups, in comparison to the other groups (p < 0.05). Enhanced CB2 immunolabeling was observed in the periodontal tissues in the EP-EA group, when compared to the EP and EP-EA-sham groups (p < 0.05). Increased CB1 immunofluorescent staining was observed in the neural tissues in the EA treated group in comparison with the other groups (p < 0.05), while no expression of CB2 was observed in those regions. Our study showed that in the presence of inflammatory bone disease, EA treatment reduced bone erosion and increased the immunoexpression of CB1 in the neural tissues and CB2 in the periodontal tissues.
Keywords: Alveolar bone loss; CB1 receptor; CB2 receptor; Chronic periodontitis; Electroacupuncture